2021
DOI: 10.1080/00224499.2021.1962236
|View full text |Cite
|
Sign up to set email alerts
|

“You’re Gay, It’s Just What Happens”: Sexual Minority Men Recounting Experiences of Unwanted Sex in the Era of MeToo

Abstract: Our grounded theory analysis derives from in-depth interviews conducted with 24 gay, bisexual, queer, and other men who have sex with men (GBM) living in Toronto, Canada, to understand their experiences of sexual coercion. Participants drew on discourse from the #MeToo movement to reconsider the ethics of past sexual experiences. The idea that gay or queer sex is inherently risky and unique from heterosexual relations made negotiating sexual safety challenging. These notions were enforced by homophobic discour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…The layout of alcohol-intensive environments being a barrier to bystander intervention is particularly concerning when 84% of our reported situations where a participant had an opportunity to bystand were in these settings. Second, consistent with prior research (Gaspar et al, 2021; McKie et al, 2020), some SGM men reported that unwanted touching is normative in alcohol-intensive and highly sexualized environments, like the environments participants described in their responses. Thus, witnessing such behavior in an alcohol-intensive environment may not automatically be perceived as concerning and not cue men into seeing a situation as worthy of their involvement.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The layout of alcohol-intensive environments being a barrier to bystander intervention is particularly concerning when 84% of our reported situations where a participant had an opportunity to bystand were in these settings. Second, consistent with prior research (Gaspar et al, 2021; McKie et al, 2020), some SGM men reported that unwanted touching is normative in alcohol-intensive and highly sexualized environments, like the environments participants described in their responses. Thus, witnessing such behavior in an alcohol-intensive environment may not automatically be perceived as concerning and not cue men into seeing a situation as worthy of their involvement.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, there is a broader (hetero)gender perception that men are always willing to have sex, suggesting they cannot be victims of sexual assault (Jozkowski & Peterson, 2013). Additionally, unwanted sexual touching and sexual violence may be normalized within the SGM community (Gaspar et al, 2021; Salter et al, 2021). Risk identification for SGM men may be complicated then by norms surrounding gender and sexuality which inform SGM men that intervention is not needed for other SGM men.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, aligning with the work of Good and Cooper (2016), our data has confirmed the blurred lines of what is considered sexual harassment in this context, suggesting that the (hyper)sexualization of labor becomes the driver for normalization and consent of sexual harassment by the customer. In doing so, we also contribute to existing research suggesting that in gay community environments, sexual consent is assumed and expected (Gaspar et al, 2021;Sternin et al, 2022), leaving workers vulnerable to sexual harassment by customers. Indeed, the evident lack of policies and processes in organizations noted by authors such as Dawson et al (2021), Poulston (2008) and Yagil (2008) to address the issue suggests that sexual harassment is an accepted (mis)behavior by customers.…”
Section: Discussionmentioning
confidence: 90%
“…Gaspar et al. (2021; p. 1206) refer to discourses which regularly present GBM as highly sexually active, sexually desirous, and sexually assertive, which complicates sexual coercion within this population, generating perceptions of ‘assumed consent’ within a ‘culture of silence’ to sexual violence and a sense of entitlement to sexual advances. Sternin et al.…”
Section: Gay Tourism and The Neglected Area Of Same Sex Harassment An...mentioning
confidence: 99%
See 1 more Smart Citation